Refrigeration in America - Anderson, Oscar Edward (Book collections on Project MUSE., 2015)
A comprehensive study of refrigeration from its beginnings in America up to 1950, which shows its relation to our national development, records the main trends in technological progress, describes the use of refrigeration, and gives some indication of its social effects. Originally published in 1953. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.